The role of microRNAs in prostate cancer migration, invasion, and metastasis - Aghdam, Shirin Golabi; Seyfizadeh, Narges (Journal of cellular physiology, 2019)
Prostate cancer (PCa) is considered the most prevalent malignancy and the second major cause of cancer-related death in males from Western countries. PCa exhibits variable clinical pictures, ranging from dormant to highly metastatic cancer. PCa suffers from poor prognosis and diagnosis markers, and novel biomarkers are required to define disease stages and to design appropriate therapeutic approach by considering the possible genomic and epigenomic differences. MicroRNAs (miRNAs) comprise a class of small noncoding RNAs, which have remarkable functions in cell formation, differentiation, and cancer development and contribute in these processes through controlling the expressions of protein-coding genes by repressing translation or breaking down the messenger RNA in a sequence-specific method. miRNAs in cancer are able to reflect informative data about the current status of disease and this might benefit PCa prognosis and diagnosis since that is concerned to PCa patients and we intend to highlight it in this paper.
First published: 07 December 2018
Gesehen am 02.05.2019